Waste To Product: Potential Of Concrete Waste Additive For Strength Improvement Of Peat Soil - Norazlina, Razizi (2023)
Peat soils are damp in their natural form, with a very high water table at the soil surface. They are also soft since they are organic (mostly composed of decomposing plant components) in nature. Peat soils are hence also known as organic soils. Peat soils have a low bulk density since they are organic in nature. Peat soils get damp due to the high water table and soft quality of the soil, and it is difficult to walk on an undrained peat soil without sinking. As a result, many soil surveyors dislike surveying virgin peat soil regions. Virgin lowland peat lands in Malaysia are frequently inundated and marshy. Because of this, several peat bogs were designated as swamps. They were not farmed and were kept unspoiled. However, as development advanced, more and more mineral (nonorganic) soils were depleted, and the peat swamps' borders were approached. In certain places of Malaysia, like in our study where we obtained samples from Pekan to Gebeng, there are few options for what sort of land to use because the state has huge sections of peat land. This study aims to comprehend the stabilisation of peat soil with waste products subjected to raise the unconfined compressive strength of the soil in order to improve the shear strength of the peat soil. Peat was stabilised using a concrete waste-derived additive. The ideal dosage of these compounds was utilised in the earlier study ratio. The effect of strength increase employing the stabilising approach was examined using the unconfined compressive strength test (UCS) at two (2) distinct curing days, namely 7 and 28 days of air curing. Results showed that concrete waste additive considerably increased the peat soil's strength. This work enhances the qualities of poor soils by making industrial and institutional waste more useful.